The Influence of Attitudes, Subjective Norms, Perception of Behavioral Control, and Product Attributes on Salvaco Cooking Oil Purchase Decisions - Alif, Muhammad Farras; Asnawi, Yudha Heryawan; Hannan, Sufrin (Indonesian Journal of Multidisciplinary Science, 2025)
The aims of this research are (1) to identify the consumer characteristics of Salvaco cooking oil (2) to analyze the influence of attitudes, subjective norms, behavioral control perceptions, and product attributes on the purchase decision of Salvaco cooking oil consumers (3) to formulate a marketing strategy that can be applied in the marketing of Salvaco cooking oil. Sampling is done by non-probability sampling method with purposive sampling technique. The result showed that the majority of respondents aged 26-35 years old, dominated by women as much as 60.2%, domiciled in Medan City, and working as private employees with upper middle income categories. SEM-PLS analysis results show that subjective attitudes and norms have a positive and significant effect on purchasing decisions as well as product prices and quality on product attributes have a positive and significant effect on purchasing decisions. The more positive the consumer attitude and the stronger the social drive around them, the more their tendency to buy Salvaco cooking oil will increase. Based on the results of QSPM analysis, Salvaco's first strategic priority is to expand distribution channels and digitize marketing. The second strategic priority is to increase brand awareness and add product variants. The last strategic priority is to utilize healthy products and internal raw materials for expansion into the UMKM market and premium segments.